2023
DOI: 10.2174/1871520622666220722105802
|View full text |Cite
|
Sign up to set email alerts
|

Galbanic Acid Improves Accumulation and Toxicity of Arsenic Trioxide in MT-2 Cells

Abstract: Background: Galbanic acid (GBA) is a sesquiterpene coumarin with valuable pharmacological effects. Adult T-cell lymphoma (ATL) is an aggressive lymphoid malignancy with low survival rate. Although arsenic trioxide (ATO) is a standard therapeutic agent for ATL treatment, efficacy of chemotherapy is limited due to chemoresistance of cells. Objective: The present study was carried out to investigate whether GBA in combination with ATO would improve cytotoxicity against ATL cells. Methods: GBA was isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Time-and dose-dependent toxicity of GBA has been reported in human ovarian, lung and prostate carcinoma cells, and upregulation of caspase 9, downregulation of antiapoptotic protein BCL-xL and inhibition of androgen receptor signaling pathway have been introduced as mechanisms of its anticancer action (24)(25)(26). In addition, it has been demonstrated that GBA has the potential to improve the accumulation and efficacy of arsenic trioxide in ATL cells (27). The current study is the first report indicating low doses of GBA (10 and 20 µM) induced significant toxicity on ATL cells in hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Time-and dose-dependent toxicity of GBA has been reported in human ovarian, lung and prostate carcinoma cells, and upregulation of caspase 9, downregulation of antiapoptotic protein BCL-xL and inhibition of androgen receptor signaling pathway have been introduced as mechanisms of its anticancer action (24)(25)(26). In addition, it has been demonstrated that GBA has the potential to improve the accumulation and efficacy of arsenic trioxide in ATL cells (27). The current study is the first report indicating low doses of GBA (10 and 20 µM) induced significant toxicity on ATL cells in hypoxia.…”
Section: Resultsmentioning
confidence: 99%